A novel natural-derived tilapia skin collagen mineralized with hydroxyapatite as a potential bone-grafting scaffold. (August 2022) - Yao, Shiyu; Shang, Yuli; Ren, Bo; Deng, Shu; Wang, Zhe; Peng, Yang; Huang, Zhaohui; Ma, Shiqing; Peng, Cheng; Hou, Shuai
Collagen is widely used in medical field because of its excellent biocompatibility and bioactivity. To date, collagen for biomedical use is always derived from bovine or swine. The purpose of this study was to evaluate collagen-based biomaterials from non-mammalian donors for bone repair. Thus, tilapia skin collagen-hydroxyapatite (T-col/HAp) scaffolds were fabricated in three different proportions and then cross-linked with 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide-N-hydroxysuccinimide (EDC-NHS). The scaffolds were evaluated for their microstructure, chemical and physical properties, mechanical strength and degradability. Then the in vitro responses of bone mesenchymal stem cells (BMSCs) to the scaffolds were investigated in terms of cellular proliferation, differentiation, and mineralization. At last, the scaffolds were implanted into rat skull critical defections to investigate the potential of osteogenic activities. As a result, the pore sizes and the porosities of the scaffolds were approximately 106.67–196.67 μm and 81.5%–66.7%. Pure collagen group showed a mechanical strength of 0.065 MPa, and the mechanical strength was significantly enhanced almost 17 times and 32 times in collagen/HAp ratio 1:4 and 1:9 groups. In vitro studies revealed the most prominent and healthy growth of BMSCs in collagen/HAp ratio 1:4 group. All the scaffolds showed certain osteogenic activities and those loaded with small amount of hydroxyapatite showed the strongest bioactivities. The micro-CT showed that the critical bone defect was almost filled with generated bone 6 months after implantation in collagen/HAp ratio 1:4 group. The biomechanics tests further confirmed the highest generated bone strength was in the collagen/HAp ratio 1:4 group. This study indicated aquatic collagen might be a potential alternative for type I collagen from mammals in bone tissue engineering. The combination of collagen and inorganic materials was also important and appropriate inorganic component loading can achieve both osteogenic quality and osteogenic efficiency to a certain extent.